EDEMATOUS PAPULES. II. Erythema multiforme, mosquito hypersensitivity, toxic erythema of the newborn. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Besides urticaria, mosquito hypersensitivity and erythema multiforme are considered among edematous papules. Also the so called toxic erythema of the newbom will be considered in this chapter. Even anaphylactoid purpura and even more hemorrhagic edema should be included in this chapter. However, the latter two disorders have been already treated in the chapter of purpura.